Biblizmy we współczesnej literaturze popularnej na przykładzie „Kolekcji Kryminałów” Joanny Chmielewskiej - Gorzelana, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The aim of the work is to highlight the vitality and functional diversity of biblisms in contemporary ‘low’ literature imitating everyday language. This article presents the results of the use dozens of lexical units. Sometimes biblisms are modified- most often they are mentioning modifications (eg. Man cannot live by bed alone ← Man cannot live by bread alone). Less frequently we meet shortening modifications (eg. pluck hair ←pluck the hair out) and developing ones(have some remains of oil in the head ← have oil in the head). These modifications can often be justified contextually. Biblisms used in crime novels usually emphasize the seriousness of the situation and they can also introduce an element of humor.